The Helicase and RNaseIIIa Domains of Arabidopsis Dicer-Like1 Modulate Catalytic Parameters during MicroRNA Biogenesis(1)([C])([W])([OA]) - Liu, Chenggang (American Society of Plant Biologists, 2012)
Dicer-Like1 (DCL1), an RNaseIII endonuclease, and Hyponastic Leaves1 (HYL1), a double-stranded RNA-binding protein, are core components of the plant microRNA (miRNA) biogenesis machinery. hyl1 null mutants accumulate low levels of miRNAs and display pleiotropic developmental phenotypes. We report the identification of five new hyl1 suppressor mutants, all of which are alleles of DCL1. These new alleles affect either the helicase or the RNaseIIIa domains of DCL1, highlighting the critical functions of these domains. Biochemical analysis of the DCL1 suppressor variants reveals that they process the primary transcript (pri-miRNA) more efficiently than wild-type DCL1, with both higher K(cat) and lower K(m) values. The DCL1 variants largely rescue wild-type miRNA accumulation levels in vivo, but do not rescue the MIRNA processing precision defects of the hyl1 null mutant. In vitro, the helicase domain confers ATP dependence on DCL1-catalyzed MIRNA processing, attenuates DCL1 cleavage activity, and is required for precise MIRNA processing of some substrates.